Fine Mapping of Lr49 Using 90K SNP Chip Array and Flow-Sorted Chromosome Sequencing in Wheat - Nsabiyera, Vallence; Baranwal, Deepak; Qureshi, Naeela; Kay, Pippa; Forrest, Kerrie; Valárik, Miroslav; Doležel, Jaroslav; Hayden, Matthew J.; Bariana, Harbans S.; Bansal, Urmil K. (Frontiers in Plant Science, 2020)
Leaf rust, caused by Puccinia triticina, threatens global wheat production due to the constant evolution of virulent pathotypes that defeat commercially deployed all stage-resistance (ASR) genes in modern cultivars. Hence the deployment of combinations of adult plant resistance (APR) and ASR genes in new wheat cultivars is desirable. Adult plant resistance gene Lr49 was previously mapped on the long arm of chromosome 4B of cultivar VL404 and flanked by microsatellite markers barc163 (8.1 cM) and wmc349 (10.1 cM), neither of which was sufficiently closely linked for efficient marker assisted selection. This study used high-density SNP genotyping and flow sorted chromosome sequencing to fine-map the Lr49 locus as a starting point to develop a diagnostic marker for use in breeding and to clone this gene. Marker sunKASP_21 was mapped at 0.4 cM proximal to Lr49, whereas a group of markers including sunKASP_24 were placed 0.6 cM distal to this gene. Testing of the linked markers on 75 Australian and 90 European cultivars with diverse genetic backgrounds showed that sunKASP_21 was most strongly associated with Lr49. Our results also show that the Lr49 genomic region contains structural variation relative to the reference stock Chinese Spring, possibly an inverted genomic duplication, which introduces a new set of challenges for the Lr49 cloning.